Estimation of stability of DNA-containing vegetable samples stored under the accelerated DNA degradation - V. A. Khachumov; I. V. Kornienko; A. V. Usatov (Зерновое хозяйство России, 2020)
There has been carried out an estimation of stability of DNA-containing plant samples stored under the conditions that model accelerated DNA degradation. The research material were the lines H. annuus (“VIR 114”, “VIR 116”) and wild-growing forms of sunflower H. decapetalus, H. petiolaris, H. rigidus taken from the collection of the N. I. Vavilov All-Russian Institute of Plant Genetic Resources. On average, the stability level of long DNA fragments for the nuclear, mitochondrial, and chloroplast genomes was 76.9%, 87.5%, and 98.3% respectively compared with the control. When assessing the stability of short DNA fragments, it was shown that on average, the number of nuclear, mitochondrial, and chloroplast DNA was 89.5%, 96.0%, and 97.7% respectively compared with the control.